2014
DOI: 10.1080/13691058.2014.902102
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualisations of masculinity and self-reported medication adherence among HIV-positive Latino men in Los Angeles, California, USA

Abstract: HIV-positive Latino men have been found to have poorer medication adherence compared to Whites. This study sought to identify how cultural conceptualisations of masculinity are associated with self-reported medication adherence among Latino men. 208 HIV-positive men reported the number of doses of antiretroviral medication missed in the previous seven days (dichotomised at 100% adherence versus less). Conceptualisations of masculinity consisted of traditional machismo (e.g., power and aggressive attitudes, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 40 publications
1
25
1
2
Order By: Relevance
“…Blashill and Vander Wal (2010) noted that the pressure to appear in shape and to project physical masculinity could facilitate HAART non-compliance. Galvan, Bogart, Wagner, and Klein (2012) found that, among 208 HIV+ Latino MSM, men endorsing traditional machismo (i.e., a cultural conceptualization of masculinity) were half as likely as others to report 100% adherence to medication. The side effects of HIV medication can reduce libido, virility, and erectile tumescence; these are perceived threats to masculinity and could be barriers to adherence (Halkitis, 2001).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Blashill and Vander Wal (2010) noted that the pressure to appear in shape and to project physical masculinity could facilitate HAART non-compliance. Galvan, Bogart, Wagner, and Klein (2012) found that, among 208 HIV+ Latino MSM, men endorsing traditional machismo (i.e., a cultural conceptualization of masculinity) were half as likely as others to report 100% adherence to medication. The side effects of HIV medication can reduce libido, virility, and erectile tumescence; these are perceived threats to masculinity and could be barriers to adherence (Halkitis, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…These men were more likely to seek medical help, going against traditional masculine norms. Additionally, Galvan et al (2012), found that “caballerismo,” a culture-specific conceptualization of masculinity that stresses collaboration, family values, and respect, was significantly correlated to an increased likelihood of reporting 100% compliance with HIV medication. Many of these gender-transformative interventions were designed for heterosexual men in countries outside of the United States; the present analysis calls attention to the need for exploration of their effectiveness with MSM in the US as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; the second, caballerismo , represents cultural ideals of men’s honor, integrity, fairness, cooperation, respect for elders, importance of family, etc. (Arciniega, Anderson, Tovar-Blank, & Tracey, 2008; Galvan, Bogart, Wagner, Klein, & Chen, 2014; Ojeda, Rosales, & Good, 2008). Typically, machismo is framed as a risk factor, and caballerismo is framed as a protective factor (Arciniega et al, 2008; Ojeda & Piña-Watson, 2014).…”
Section: Race-ethnicity and Gender As Moderatorsmentioning
confidence: 99%
“…Durante el proceso de tratamiento, los varones que viven con VIH pueden considerar que adquieren una "masculinidad deteriorada" debido a la pérdida de poder físico, de autoridad en la familia o de estatus social, la dependencia del cuidado del otro, el no poder ejercer el rol de proveedor, la disminución de la actividad sexual (ya sea por el estigma o cambios físicos) o el aislamiento de espacios sociales masculinos donde se realizan prácticas de riesgo (Lynch, Brouard, & Visser, 2010;Mfecane, 2008;Siu, Wight & Seeley, 2014). Asimismo, la presencia de masculinidades "machistas" que promueven el mantenimiento del control y la negación de la vulnerabilidad asociada al VIH se ha asociado con una menor adherencia (Galvan, Bogart, Wagner, Klein, & Chen, 2014).…”
Section: Introductionunclassified